The effects of civil unrest on tourism businesses in Vhembe Region, South Africa - Hlungwani, Rirhandzu Eunice (My University, 2021)
The study investigated the effects of civil unrest on tourism business in Vuwani area in the Vhembe region. A quantitative research approach was used in the study. The descriptive research design was adopted in conducting this research. The study population comprised of tourism stakeholders such as tourists, local residents, tour guides, tour operators and hotel managers. A stratified random sampling technique was used to select 250 respondents for the study. Questionnaires were administered to collect quantitative data. Data was analysed using the Statistical Package for the Social Sciences (SPSS) version 25. The study established that civil unrest negatively affects the local area by causing environmental degradation, political instability and negative economic activities that have a knock-on effect on the tourism business. The study recommends that the local municipality support effective service delivery, active participation of local residents in the tourism business and organise workshops to facilitate collaboration among various stakeholders to create a conducive climate for tourism development.
MCom (Business Management)
Department of Tourism and Hospitality Management
Keywords: Civil unrest; UCTD; Tourism business; Local residents; Tour guides; Tour operators; Hotel managers